Reviews of Books (International review of mission, 1962)
THE CHALLENGE OF SOCIAL CHANGE: MAN IN RAPID SOCIAL CHANGE. By Egbert de Vries. THE CHALLENGE OF SOCIAL CHANGE: THE CHURCHES AND RAPID SOCIAL CHANGE. By Paul Abrecht. STUDIES OF AFRICAN SOCIETY: SOCIAL CHANGE IN MODERN AFRICA: Studies presented and discussed at the Firsts International African Seminar, Makerere College, Kampala, January, 1959. Edited, with an introduction, by Aidan Southall. STUDIES OF DISSENT: ENGLISH RELIGIOUS DISSENT. By Erik Routley. STUDIES OF DISSENT: ROOTED IN FAITH. By F. G. Haeley. STUDIES OF DISSENT: AN ERRAND OF MERCY. By Charles I. Foster. OUT OF CONTEMPLATION: EX CONTEMPLATIONE LOQUI. Gesammelte Aufsätze von Thomas Ohm. CHRISTIAN HISTORY IN KOREA: L'ERECTION DU PREMIER VICARIAT APOSTOLIQUE ET LES ORIGINES DU CATHOLICISME EN CORÉE. 1592–1837. By Andreas Choi. A STUDY OF WORSHIP: WORKSHIP IN THE NEW TESTAMENT. By C. F. D. Moule. SUNDAR SINGH: SUNDAR SINGH: EIN INDISCHER ZEUGE DES LEBENDIGEN CHRISTUS. By A. J. Appasamy. JUDAISM AND CHRISTIANITY: CHRISTENTUM UND JUDENTUM IN DER SCHAU LEO BAECKS. By Reinold Mayer. THE AFRICAN WOMAN: LA CONDITION DE L'AFRICAINE EN AFRIQUE NOIRE. By F. Plisnier-ladame. THE CHURCH AND AFRICAN CUSTOMARY LAW: L'EMPÊCHEMENT DE ‘PARENTÉ’ EN DROIT COUTUMIER AFRICAIN. By Jan van Driessche, SJ. SOUTH AFRICA—AN INCURABLE CASE?: SOUTH AFRICA, REVOLUTION OR RECONCILIATION? By Ambrose Reeves. SOUTH AFRICA—AN INCURABLE CASE?: LIBERTY, EQUALITY, FRATERNITY—TO-DAY. By D. V. Cowen. SOUTH AFRICA—AN INCURABLE CASE?: THE ANATOMY OF SOUTH AFRICAN MISERY. By C. W. De Kiewiet. SOUTH AFRICA—AN INCURABLE CASE?: MULTI-RACIAL SOUTH AFRICA: THE RECONCILIATION OF FORCES. By Z. J. De Beer. AFRICAN ELECTION REALITIES: THE KENYATTA ELECTION: Kenya 1960–1961. By George Bennett and Carl Rosberg. STUDIES OF CONGO TRADITIONS: ETUDES BAKONGO: SOCIOLOGIE—RELIGION ET MAGIE. By J. van Wing, SJ. FEUDALISM IN AFRICA: THE PREMISE OF INEQUALITY IN RUANDA: A STUDY OF POLITICAL RELATIONS IN A CENTRAL AFRICAN KINGDOM. By Jacques J. Maquet. PRESENTATIONS OF THE FAITH: INTRODUCING CHRISTIANITY. By E. H. Pyle and S. G. Williamson. PRESENTATIONS OF THE FAITH: THEY WHO WILL HEAR. By Allen Birtwhistle. GUIDES TO BIBLE STUDY: BIBLE GUIDES. Edited by WILLIAM BARCLAY and F. F. BRUCE. No. 1: THE MAKING OF THE BIBLE. By WILLIAM BARCLAY. No. 7: PROPHETS OF ISRAEL (1) ISAIAH. By GEORGE KNIGHT. No. 11: THE WISDOM OF ISRAEL. By JOHN PATERSON. No. 13: THE GOOD NEWS. By C. L. MITTON. SOURCE-MATERIALS ON EAST AFRICA: EAST AFRICA THROUGH CONTEMPORARY RECORDS. Selected and Introduced by Zoë Marsh. SOUTH AMERICAN HORTICULTURAL SYSTEMS: THE EVOLUTION OF HORTICULTURAL SYSTEMS IN NATIVE SOUTH AMERICA: CAUSES AND CONSEQUENCES: A SYMPOSIUM. Edited By Johannes Wilbert.